(untitled) (Delta Medical College Journal, 2024)
Background: Coronavirus Disease 2019 (COVID-19) is an acute respiratory disease that can present varieties of clinical and pathologic manifestation. Sometimes it present with severe manifestation which ultimately lead to respiratory failure and death. COVID-19 patients with other comorbidities may develop a life-threatening situation. Objective: To describe the clinicopathologic features and outcome of COVID-19 patients admitted in Combined Military Hospital (CMH) Rangpur, Bangladesh. Materials and method: This cross-sectional study was conducted at CMH Rangpur, Bangladesh, from 1 May 2021 to 30 August 2021 among purposively selected 416 cases of COVID-19 positive patients. Data were collected from the medical records of the hospital admitted patients in a structured case report form. Results: Highest numbers of the respondents were in the age group of 31-50 years (49.03%) with male predominance (72.28%). About 89% were Muslim and 54.81% were educated up to higher secondary level. Fever (90.86%) was the common presenting symptoms followed by cough (73.55%), sore throat (30.28%). About 24.51%, 23.07%, 11.05% had hypertension, diabetes mellitus and respiratory comorbidities respectively. Lymphopenia (75.24%) and elevated C-Reactive Protein (54.08%) were observed in most of the cases. Only 8.17% patients had critical illness that needed intensive care unit admission. Majority (91.82%) fully recovered from the illness while 1.92% expired. Conclusions: The most commonly reported symptom was fever (90.86%) among all the COVID-19 positive patients. Majority (62.25%) of the patients belonged to mild cases. Overall mortality was 1.92%. In most cases the clinical presentation is that of a respiratory infection with symptom severity ranging from a mild influenza like illness. Delta Med Col J. Jan 2021;9(1):3-8